Stroke and Cardiovascular Outcomes in Patients With Carotid Disease Undergoing Transcatheter Aortic Valve Replacement. (June 2018) - Kochar, Ajar; Li, Zhuokai; Harrison, J. Kevin; Hughes, G. Chad; Thourani, Vinod H.; Mack, Michael J.; Matsouaka, Roland A.; Cohen, David J.; Peterson, Eric D.; Jones, W. Schuyler; Vemulapalli, Sreekanth
Abstract : Background—: Stroke is a serious complication of both transcatheter aortic valve replacement (TAVR) and carotid artery disease (CD). The implications of CD in patients undergoing TAVR are unclear. Methods and Results—: The Society of Thoracic Surgeons and American College of Cardiology Transcatheter Valve Therapies Registry, consisting of data from consecutive US TAVR cases during the years 2013 to 2015, was linked to Medicare claims data to ascertain 30-day and 1-year cumulative incidence rates of stroke and all-cause mortality. We compared 30-day and 1-year stroke and mortality outcomes between patients with no-CD and patients with moderate, severe, and occlusive CD and adjusted for baseline covariates using proportional hazards models. Among 29 143 patients undergoing TAVR across 390 US sites, 22% had CD. Patients with CD had higher rates of prior hypertension, diabetes mellitus, stroke, and myocardial infarction. Observed in-hospital stroke rates were 2.0% among no-CD, 2.5% among moderate CD, 3.0% among severe CD, and 2.6% among occlusive CD. There was no association between the presence of CD and 30-day stroke (adjusted hazard ratio, 1.16; 95% confidence interval, 0.94–1.43) or mortality (adjusted hazard ratio, 1.10; 95% confidence interval, 0.95–1.28). There was no association between CD and 1-year stroke (adjusted hazard ratio, 1.03; 95% confidence interval, 0.86–1.24) or mortality (adjusted hazard ratio, 1.02; 95% confidence interval, 0.93–1.12). Furthermore, there was no significant risk-adjusted association between severity of CD and 30-day or 1-year stroke or mortality. Conclusions—: CD is common among TAVR patients, present in 1 of 5. CD was not associated with an increased risk of stroke or mortality at 30 day or 1 year. Post-TAVR stroke seems to be because of mechanisms other than CD. Abstract : Supplemental Digital Content is available in the text.